2022
DOI: 10.1039/d2se00027j
|View full text |Cite
|
Sign up to set email alerts
|

The potential scarcity, or not, of polymeric overall water splitting photocatalysts

Abstract: We perform a high-throughput virtual screening of a set of 3240 conjugated alternating binary co-polymers and homo-polymers, in which we predict their ability to drive sacrificial hydrogen evolution and overall...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…In principle, predictions have shown that a large number conjugated polymers are thermodynamically able to perform overall water splitting [ 188 ] and more studies need to focus on the design of materials that facilitate this to drive this area of research forward. Related to this, it will be important to study metal cocatalysts for overall water splitting and we expect that significant performance gains are possible based on what has been observed for inorganic semiconductor photocatalysts [ 189 ].…”
Section: Discussionmentioning
confidence: 99%
“…In principle, predictions have shown that a large number conjugated polymers are thermodynamically able to perform overall water splitting [ 188 ] and more studies need to focus on the design of materials that facilitate this to drive this area of research forward. Related to this, it will be important to study metal cocatalysts for overall water splitting and we expect that significant performance gains are possible based on what has been observed for inorganic semiconductor photocatalysts [ 189 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the success of COF SSPCs in photocatalytic hydrogen evolution, water oxidation photocatalysts supporting oxygen evolution are required to achieve overall solar water splitting. However, since the complex four-electron transfer process of oxygen formation leads to particularly sluggish reaction kinetics, it remains challenging to develop viable COF SSPCs active for oxygen evolution, even though a certain amount of COFs are expected to be thermodynamically capable of oxidizing water and evolving oxygen . For example, Chen et al demonstrated a Co 2+ functionalized bpy-COF (BpCo-COF-1), which enabled photocatalytic oxygen evolution in the presence of AgNO 3 as sacrificial electron acceptor (SEA) .…”
Section: Solar-driven Water Splittingmentioning
confidence: 99%
“…However, since the complex four-electron transfer process of oxygen formation leads to particularly sluggish reaction kinetics, it remains challenging to develop viable COF SSPCs active for oxygen evolution, even though a certain amount of COFs are expected to be thermodynamically capable of oxidizing water and evolving oxygen. 47 For example, Chen et al demonstrated a Co 2+ functionalized bpy-COF (BpCo-COF-1), which enabled photocatalytic oxygen evolution in the presence of AgNO 3 as sacrificial electron acceptor (SEA). 48 Loading 1 wt % Co 2+ onto the COF resulted in an optimal oxygen evolution rate of 152 μmol g −1 h −1 , while higher Co 2+ loadings resulted in a decreased activity.…”
Section: ■ Solar-driven Water Splittingmentioning
confidence: 99%
“…Nevertheless, this requirement alone is insufficient for enabling overall water-splitting reactions since different combinations of conduction band (CB) and valence band (VB) can result in the same band gap energy. To fulfill the criteria, the CB must have a more negative potential than that of the proton reduction reaction, while the VB must have a more positive potential than that of the water oxidation reaction 7 12 . The demanding specifications of the photocatalyst material, therefore, pose significant limitations and challenges in the selection of suitable materials for overall water-splitting reactions 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…To fulfill the criteria, the CB must have a more negative potential than that of the proton reduction reaction, while the VB must have a more positive potential than that of the water oxidation reaction 7 12 . The demanding specifications of the photocatalyst material, therefore, pose significant limitations and challenges in the selection of suitable materials for overall water-splitting reactions 11 , 12 . On the other hand, numerous studies have reported the effective utilization of a sacrificial hole scavenger to enhance the photocatalytic production of hydrogen from water.…”
Section: Introductionmentioning
confidence: 99%